Changing One's Mind when the Facts Change: Incentives of Experts and the Design of Reporting Protocols - Li, Wei (Review of Economic Studies, 2007)
Experts often collect and report information over time. What reporting protocol elicits the most information? Here, a principal receives reports sequentially from an agent with privately known ability, who observes two signals about the state of the world. The signals differ in initial quality and, unlike previous work, differ in quality improvement. The paper finds that “mind changes” (inconsistent reports) can signal talent if a smart agent improves faster. Also, sequential reports dominate when the principal's decision is very sensitive to information; a single report dominates if the mediocre agent's signals improve faster or the agent is likely mediocre.